Influence Of Environment On Different Personality Of The Twins In Rainbow Rowell's Fangirl (2013): A Behaviorism Perspective - HIDAYAH, Hana Nur; , Dr. Muhammad Thoyibi, M. S. (2017)
This study is about different personality of the twins because influence of environment in Fangirl of Rainbow Rowell (2013) which is analyzed by using Behaviorism Perspective. The objectives of the study are to know the factors of influence of environment, to know the reason why Rainbow Rowell addressed the twins in the Fangirl novel based on Behaviorism Perspective. The research belongs to in qualitative research. The primary data of this research is Fangirl novel by Rainbow Rowell in 2013, while the secondary data of this research are other source related to the study, such as: website, dictionary and some books which support this research. The researcher draws three conclusions in this research. Firstly different personality between Wren and Cath,the researcher just to find three point which can different personality in the novel Fangirl that are: based on their opinion, attitude, and acts of their respectively. Secondly, the factors of environment which can influence of their personality. Third is the underlying reason why Rainbow Rowell address twin in her novel is to show of the different caracter in the family as the occurred her it. Rowell has two sons which alway different opinion and to help progress her story